Standardy społecznej odpowiedzialności małego biznesu. Analiza porównawcza firm polskich i brytyjskich - Lewicka-Strzałecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2008)
The aim of this article is to discern the crux of SME sector social responsibility in developing countries. An attempt is made to identify, empirically, the ethical standards subscribed to by small firms in Poland and to compare them with the standards of small firms in the UK. The methodology of empirical analysis of the ethical standards of Polish entrepreneurs running small businesses was modelled on Laura Spence’s research on the priorities, practices and ethics of small firms in the UK. This analysis has revealed certain similarities and significant differences in the way CSR is perceived by Polish and British entrepreneurs. British entrepreneurs manifest a higher degree of awareness with regard to the issue of social responsibility and are more strongly motivated by their external environment to take up social responsibility issues than Polish ones.